Bandwidth enhancement for Ka-band metasurface antenna using bound TM10 and TE20 resonances and decoupled antiphase TM20 resonance - Yuxiang Zheng; Quanlu Zhao; Xin Zhang; Liqiang Cao; Qidong Wang; Weikang Wan (AIP Advances)
A bandwidth enhancement mechanism based on metasurface (MTS) is proposed. The pre-designed stack-patch determines the baseline bandwidth limitation. The triple resonances of MTS enhance the in-band impedance match. The E-plane MTS dominates the lowest bound transverse magnetic (TM) TM10 leaky-wave resonance. The H-plane MTS facilitates the adjustment of the middle decoupled antiphase TM20 resonance. The cavity size along the H-field direction determines the highest bound transverse electric (TE) TE20 surface-wave resonance. Using the proposed physical model, a miniaturized antenna configuration is designed and implemented. A capacitance-loaded mechanism reveals the feasibility of MTS miniaturization. The interaction of MTS modes achieves a larger −10 dB impedance bandwidth (IMBW) of 40.1% or a larger −15 dB IMBW of 25.7% with high manufacturing robustness, demonstrating the suitability of millimeter-wave antennas for broadband applications. According to the −15 dB IMBW design standard, a fabricated antenna features a compact aperture size of 0.47λ0× 0.47λ0 and a low profile of 0.063λ0 (λ0 is the free space wavelength at the center operating frequency, and profile is the distance from the first metal layer to GND). This design shows significant potential for Ka-band antenna-in-package (AiP) applications in 5.5G communication systems.